Calibration of Surface Plasmon Resonance Imager for Biochemical Detection - T. Ktari; H. Baccar; M. B. Mejri; A. Abdelghani (International Journal of Electrochemistry)
We present a new Surface Plasmon Resonance imager (SPRi) based on immobilized T4-phage for bacteria detection. First, we present the sensitivity of the SPR imager towards refractive index variation for biosensor application. The SPR imager can be calibrated versus different percentage of triethylene glycol mixture in ultrapure water. The system can be used as a refractometer with sensitivity below 5×10−5 in the range of 1.33300–1.34360. Second, bacteriophage (T4-phage) can be physisorbed on gold microarray spots for bacteria detection. The kinetic physisorption of different concentrations of T4-phages can be observed in real time. Finally, two types of bacteria such as E. coli (gram negative) and Lactobacillus (gram positive) were used for positive and negative tests. The results show a selectivity of T4-phage toward E. coli with a detection limit below 104 CFU/mL and with good reproducibility.